2019
DOI: 10.1177/0743915619875419
|View full text |Cite
|
Sign up to set email alerts
|

Filling in the Blanks: What Restaurant Patrons Assume About Missing Sanitation Inspection Grades

Abstract: How do people respond when decision-relevant information is withheld by sellers? The authors address this general question by examining how prospective diners respond when sanitation inspection grades (SIGs) are not reported by a restaurant. Despite disclosure mandates in some municipalities, SIGs are not always available when dining choices are made, especially when food is ordered for delivery. After documenting participants’ failure to discount appropriately for a missing SIG, the authors demonstrate, throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Thus, words need to be converted into a numerical vector before being fed into a neural network. 6 These vectors are called “embedding,” and most well-known embedding algorithms (e.g., word2vec, GloVe) are based on the distributional hypothesis—that is, words with similar meanings tend to co-occur more frequently (Harris 1954) and thus have vectors that are close in the embedding space. The efficiency of the neural network improves manifold if these initial inputs carry meaningful information about the relationships between words.…”
Section: Converting Text Into Numeric Attribute Sentiment Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, words need to be converted into a numerical vector before being fed into a neural network. 6 These vectors are called “embedding,” and most well-known embedding algorithms (e.g., word2vec, GloVe) are based on the distributional hypothesis—that is, words with similar meanings tend to co-occur more frequently (Harris 1954) and thus have vectors that are close in the embedding space. The efficiency of the neural network improves manifold if these initial inputs carry meaningful information about the relationships between words.…”
Section: Converting Text Into Numeric Attribute Sentiment Scoresmentioning
confidence: 99%
“…For example, Slovic and MacPhillamy (1974) and Peloza, Ye, and Montford (2015) discuss some common types of wrong inferences-higher weights on common attributes (i.e., attributes for which information is available for all options) or simply proxy a missing attribute score with some unrelated attribute score (extra-attribute misestimation). Gurney and Loewenstein (2019) provide an excellent review of this topic. Although the nature of these inferences may vary, the general takeaway is that missingness usually worsens choice and decision making.…”
mentioning
confidence: 99%
“…Therefore, it is important to study the impact of recent improvements in these presentationssuch as emoji-based displays with locality-adjusted hygiene scores. In the Finnish context, Gurney and Loewenstein (2020) found that the use of emojis to rate food establishments does influence the behaviors of customers. Here, we look at the effect on hygiene compliance by a food establishment.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Although the microbial contents of cream cakes were closely related 935398C QXXXX10.1177/1938965520935398Cornell Hospitality QuarterlyPatel and Rietveld research-article2020 1 Villanova University, PA, USA 2 Erasmus University Rotterdam, The Netherlands to the food inspectors' ranking, the microbial contents of pasta salads frequently exceeded standards in outlets with highly satisfactory rankings. In Finland, a system including both numerical information and four smiley faces was found to affect the purchase intentions of restaurant customers (Gurney & Loewenstein, 2020). Beyond Denmark and Finland, there is limited evidence on whether emojis are a useful disclosure mode.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding pre-play cheap talk among rational players gives us a benchmark for studying pre-play cheap talk in laboratory games and in the real world; a context in which players are boundedly rational, may have incomplete information, and may have uncertainty or biases about each other's social preferences [23]. These behavioral elements allow communication to be informative in new and interesting ways [24][25][26][27][28][29].…”
mentioning
confidence: 99%